Toward Permeable Boundaries of Organizations? - Ringel, Leopold; Hiller, Petra; Zietsma, Charlene (Research in the sociology of organizations, 2018)
The classical concept of organizations as solitary 'walled-in' actors with clear operational boundaries is increasingly being challenged. This volume examines why, examines the impact of these changes on organizations and offers conceptual and empirical insights.